1997
DOI: 10.1212/wnl.48.3.608
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for treatment of trigeminal neuralgia

Abstract: Sixty patients with trigeminal neuralgia who did not have a response to pharmacologic treatment (including 22 who had no response to conventional surgical treatment) underwent stereotactic radiosurgical treatment with the Leksell Gamma Knife. A radiosurgical maximum dose of 70 Gy was delivered to the trigeminal nerve root adjacent to the pons via a 4-mm collimator helmet in 51 patients who presented with trigeminal neuralgia unrelated to tumors. In these patients, the root was localized by stereotactic MRI. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 2 publications
6
74
1
Order By: Relevance
“…[4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery. Our excellent and good outcome rates are comparable to those reported in previously published studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery. Our excellent and good outcome rates are comparable to those reported in previously published studies.…”
Section: Discussionsupporting
confidence: 91%
“…Although the observed differences in outcome did not reach levels of statistical significance in our study, a history of previous surgery has been previously identified as a negative prognostic factor. 1,8,17,23,24,31 Meticulous analysis of our pain outcome data revealed that the difference in the observed excellent outcome rates between patients who had and had not undergone previous surgeries became more profound as the time progressed, reaching a maximum at posttreatment Year 6. This finding may indicate that patients with no previous surgeries not only respond better to SRS treatment but maintain their excellent or good response longer than patients with a history of previous surgery; this parameter should be seriously considered in the surgical planning for SRS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…"Some agreement with a trend" indicates that atypical facial pain could responds worse to Gamma Knife treatment. (Young, 1997) reported 88% of pain relief in 9 patient treated targeting the tumor, Regis (Regis 2001), obtained pain cessation in 79.5% of 46 patients targeting the tumor, in 3 cases the target was the nerve and in 4 the target was the tumor with the nerve together. Pollock (Pollock, 2000) treated 23 patients (16 meningiomas and 8 malignant tumors).…”
Section: Pain Distributionmentioning
confidence: 99%
“…33,69 The target has changed from the ganglion to the preganglionic root in the posterior fossa adjacent to the brainstem, which is the same area in which vascular compression is found. Concern remains about the time it takes for the treatment to achieve an effect.…”
Section: Neurosurg Focus / Volume 18 / April 2005mentioning
confidence: 99%